The Impact of the Covid-19 Pandemic on Air Traffic in the Asian Region: How the Aviation Industry Adapted Throughout the Pandemic - Thompson, Daniel; Kannan, Subarmaniam (International Journal of Membrane Science and Technology, 2023)
The COVID-19 pandemic continues to pose a global threat, profoundly impacting various sectors, including the aviation industry. This research aims to uncover the impact of the pandemic on the aviation sector in the Asian region. Specifically, it explores the mandatory compliance of social measures and vaccination requirements imposed by governments, which have become crucial factors determining the feasibility of direct or international flights. The analysis focuses on several key aspects, including air traffic data, daily COVID-19 cases, vaccination rates, and implemented social measures within the Asian region. By examining the air traffic of each successful flight from departure to arrival, valuable insights into the aviation industry's perseverance throughout the pandemic are generated. Preliminary findings reveal a sharp decline in air traffic volume by -58.68% in 2020 compared to the previous year, attributed to the significant number of COVID-19 cases reported by December 31, 2020 (totaling 19,892,098 cases). However, the deployment of vaccination doses in 2021 has resulted in a modest recovery, with air traffic volume increasing by 12.64% compared to 2020. This recovery has prompted several countries to cautiously reopen borders and transition towards the recovery phases of the pandemic, despite the ongoing prevalence of COVID-19 cases. The research provides insights into the resilience and adaptability of the aviation industry, shedding light on the challenges faced and opportunities presented during the COVID-19 pandemic. By understanding the impact of social measures and vaccination requirements, stakeholders in the aviation sector can formulate strategies to navigate the current crisis and prepare for potential future disruptions. The findings contribute to the sustainable recovery of the aviation industry by informing policymakers, airlines, and other stakeholders about the factors influencing air travel in the Asian region. The analysis of air traffic, COVID-19 cases, vaccination rates, and social measures provides a comprehensive understanding of the aviation industry's response to the pandemic.